Commercial Scale Manufacturing of Allogeneic Cell Therapy - Pigeau, Gary M.; Csaszar, Elizabeth; Dulgar-Tulloch, Aaron (Frontiers in Medicine, 2018)
Allogeneic cell therapy products are generating encouraging clinical and pre-clinical results. Pluripotent stem cell (PSC) derived therapies, in particular, have substantial momentum and the potential to serve as treatments for a wide range of indications. Many of these therapies are also expected to have large market sizes and require cell doses of ≥109 cells. As therapeutic technologies mature, it is essential for the cell manufacturing industry to correspondingly develop to adequately support commercial scale production. To that end, there is much that can be learned and adapted from traditional manufacturing fields. In this review, we highlight key areas of allogeneic cell therapy manufacturing, identify current gaps, and discuss strategies for integrating new solutions. It is anticipated that cell therapy scale-up manufacturing solutions will need to generate batches of up to 2,000 L in single-use disposable formats, which constrains selection of currently available upstream hardware. Suitable downstream hardware is even more limited as processing solutions from the biopharmaceutical field are often not compatible with the unique requirements of cell therapy products. The advancement of therapeutic cell manufacturing processes to date has largely been developed with a cell biology driven approach, which is essential in early development. However, for truly robust and standardized production in a maturing field, a highly controlled manufacturing engineering strategy must be employed, with the implementation of automation, process monitoring and control to increase batch consistency and efficiency.